Factors Affecting Environmental Coherence of Community: Adolescence's Perception on Neighborhood Dwelling Resemblance - Supoj Prompayuk; Nopadon Sahachaisaeree (My University, 2012)
The over resemblance of architectural features often creates a built-environment with monotonous and placelessness. This research attempts to examine the perception of both architects and adolescence lay persons on their perceptions over design element configurations. A set of simulated photographic stimuli embedded with relevant variables are utilized to persuade answers between two groups of respondents on their perceived unity in the neighborhood. The research suggested that, in order to create a united appearance and avoid placelessness of the neighborhood, architect must pay close attention to window and door consistency which could help create environmental harmony without boring side effects.
Keywords: Harmony (Music); Sense of Place; Place Attachment; Sense of Community; Place Attachment and Urban Studies